Clinical evaluation of children with hematuria at the primary care level - T.P. Borysova; Z.S. Allahverdieva (Zaslavsky O.Yu., 2020)
Hematuria is the presence of five or more red blood cells in three consecutive urinalyses obtained with an interval of one week. At the level of primary medical care, the doctor must be able to recognize and confirm the presence of hematuria, suggest its possible causes, and select patients who could potentially have a serious illness of the urinary system. The algorithm for providing primary medical care for hematuria in children depends on its clinical variant: macrohematuria, symptomatic microhematuria, asymptomatic microhematuria with proteinuria, asymptomatic isolated microhematuria. Examination which is indicated for children with macrohematuria is: general urine analysis, complete blood count, serum creatinine, calcium/creatinine ratio in a urine sample, ultrasound of the kidneys and bladder. If, as a result of clarification of complaints, medical history, physical and additional examinations, the cause of macrohematuria is not established, the child should be referred to a pediatric nephrologist. Evaluation of children with symptomatic microhematuria is aimed at identifying common (fever, malaise, abdominal pain, etc.), non-specific (rash, arthritis, jaundice, respiratory, gastrointestinal symptoms, etc.) and specific to the urinary system symptoms (dysuria, pollakiuria, urinary incontinence, enuresis, edema, hypertension). The presence of hematuria in combination with proteinuria in children most often suggests the glomerular origin of hematuria. Asymptomatic patients with hematuria and proteinuria persistent for 2-3 weeks should be referred to a pediatric nephrologist for further examination. Asymptomatic isolated microhematuria is the most common type of hematuria in children, it is usually short-term and, as a rule, is not associated with severe renal disease. The most common causes of asymptomatic microhematuria persisting for more than six months are IgA nephropathy, thin basement membrane disease, and hereditary nephritis (Alport syndrome), hypercalciuria, urinary tract infection are less common. At the stage of further examination and further observation of children with asymptomatic isolated microhematuria, the optimal treatment is the phytoneering drug Canephron® N.